Building Custom Components and Services in Angular 2+ - Manasa Talluri (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
Angular 2+ represents a significant advancement in web application development, offering a structured and component-driven approach to building highly interactive and scalable single-page applications. At the heart of Angular’s architecture are custom components and services, which together enable developers to create modular, reusable, and maintainable code. Components are the building blocks of the user interface, encapsulating both the structure and behavior of specific views, while services are instrumental in managing data logic, business rules, and external communications. This paper explores the process of creating and integrating custom components and services within the Angular 2+ ecosystem. It discusses best practices in component design, such as separation of concerns, lifecycle management, and change detection strategies, and provides a detailed guide on service creation, including the use of observables, dependency injection, and stateless design patterns. Furthermore, the paper examines methods for optimizing performance, facilitating inter-component communication, and testing both components and services for reliability and scalability. Through a synthesis of scholarly articles, technical blogs, and practical case studies, this research aims to equip developers and software architects with comprehensive knowledge to harness the full potential of Angular 2+ for modern application development.